Considerations for Rice (Oryzasativa) Fortification with Essential Micronutrients in Public Health Intervention - Giasuddin, ASM; Jhuma, Khadija Akther; Hossain, Md Sabir; Haq, AM Mujibul (Bangladesh Journal of Medical Science, 2020)
Background and Rationale: Fortification of staple foods and commonly used condiments with vitamins and minerals has been considered one of the most cost-effective interventions to prevent and control micronutrient deficiencies. Because of its wide local consumption, acceptability, reach, and quantum of consumption, rice (Oryzasativa) far exceeds the requirements of a staple food vehicle that can be considered for fortification purposes at a population-level intervention. The World Health Organization (WHO) has the mandate to develop evidenceinformed guidelines for the fortification of staple foods as a public health intervention, including rice fortification with micronutrients. The WHO, in collaboration with the Global Alliance for Improved Nutrition (GAIN), convened a consultation on “Technical Considerations for Rice Fortification in Public Health” in Geneva, Switzerland in 2012 to provide technical inputs to the guideline development process, particularly with reference to feasibility and implementability. Conclusion: The industrial and regulatory technical considerations in rice fortification, as well as the considerations for implementing it as a public health strategy and assuring equitable access and universal coverage and priority research areas for the forthcoming years were reviewed in this article based on WHO consultation Bangladesh Journal of Medical Science Vol.19(2) 2020 p.189-193